The Transmitters - Morales-Munoz, B; Zeise-Ssa., M (Springer International Publishing, 2020)
Synaptic transmission is both, an essential process in the functioning of our brain and the most important site for plastic changes, at least in the short and medium term. There are many endogenous substances that act at (chemical) synapses. Quantitatively, by far the most important ones are the transmitters glutamate, GABA, and acetylcholine. Together with glycine, some agonists at purinergic, TRP-like receptors and one type of monoamine transmitter receptor, they are in charge of rapid, precise, and localized transmission via ionotropic receptors. The transmitters mentioned and all others act on metabotropic receptors generating slower, but long-lasting, versatile, and amplified responses. Further, there are substances that influence synaptic transmission, but are not stored in synaptic vesicles, such as retrograde messengers. Neuropharmacology, to a large part, is the science of interaction between ligands and transmitter receptors. The majority of mental pathologies have to do with imbalances and/or malfunctioning of transmitter systems. It is worthwhile, therefore, for professionals interested in neuroscience to have a thorough knowledge of the principal transmitter systems. © Springer Nature Switzerland AG 2021.